2017
DOI: 10.1016/j.thromres.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Normal pregnancy is associated with an increase in thrombin generation from the very early stages of the first trimester

Abstract: Thrombin generation increases significantly during the very early stages of normal pregnancy when compared to the pre-pregnancy state. The increased risk of venous thrombosis therefore likely begins very early in a woman's pregnancy, suggesting that women considered clinically to be at high thrombotic risk should start thromboprophylaxis as early as possible after a positive pregnancy test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Plasma mean StartTail time, peak thrombin generation and endogenous thrombin potential increased significantly in the first trimester of pregnancy and remained stable in the next two trimesters in a Chinese study [20]. Indeed, an increase of velocity index, peak thrombin and endogenous thrombin potential at the 32 nd day of gestation [21] and at the 43 rd day of gestation [22], compared to pre-pregnancy values, have been observed in two studies done in the U.K. These increased values persisted through to the 59 th day of gestation [22].…”
Section: Coagulation During Pregnancymentioning
confidence: 90%
See 2 more Smart Citations
“…Plasma mean StartTail time, peak thrombin generation and endogenous thrombin potential increased significantly in the first trimester of pregnancy and remained stable in the next two trimesters in a Chinese study [20]. Indeed, an increase of velocity index, peak thrombin and endogenous thrombin potential at the 32 nd day of gestation [21] and at the 43 rd day of gestation [22], compared to pre-pregnancy values, have been observed in two studies done in the U.K. These increased values persisted through to the 59 th day of gestation [22].…”
Section: Coagulation During Pregnancymentioning
confidence: 90%
“…Indeed, an increase of velocity index, peak thrombin and endogenous thrombin potential at the 32 nd day of gestation [21] and at the 43 rd day of gestation [22], compared to pre-pregnancy values, have been observed in two studies done in the U.K. These increased values persisted through to the 59 th day of gestation [22]. Serum levels of estradiol and progesterone were also significantly higher by day 32 of gestation.…”
Section: Coagulation During Pregnancymentioning
confidence: 91%
See 1 more Smart Citation
“…It has been demonstrated that thrombin (resulting from prothrombin) generation increased during pregnancy, starting with the very early stages of the first trimester of normal pregnancy. [8] We did not determine thrombin values, but prothrombin time was within normal limits in healthy pregnant patients.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the risk of bleeding during prenatal and postpartum period and to maintain placental function during pregnancy and delivery, physiological hypercoagulability accompanies the whole pregnancy time 1 . Abnormal coagulation and fibrinolytic system are likely to lead to a risk of venous thromboembolism (VTE) 50 times higher in pregnant women than in general population, 2 and venous thromboembolism (VTE) is one of the major obstetric causes of maternal mortality 3 …”
Section: Introductionmentioning
confidence: 99%